Empowerment and HIV Risk Behaviors in Couples: Modeling the Theory of Gender and Power in an African Context - Makhabele Nolana Woolfork; Ashley Fox; Andrea Swartzendruber; Stephen Rathbun; Joel Lee; Jane N. Mutanga; Amara E. Ezeamama (Mary Ann Liebert, 2020)
Background: Young women and girls in Eastern and Southern Africa are at elevated risk of acquiring human immunodeficiency virus (HIV) compared with men, largely due to power dynamics within heterosexual relationships that contribute to HIV risk behaviors. Few studies employ a comprehensive framework to examine divisions between men and women and HIV risk behaviors in an African context. Thus, we examined associations between levels of women's empowerment and HIV risk behaviors applying the Theory of Gender and Power. Methods: We used logistic regression (adjusted odds ratios or AORs) to assess associations between women's empowerment indicators and HIV risk behaviors (multiple sexual partners) and self-efficacy (ability to negotiate sex/sex refusal) with couples data (n?=?12,670) from Malawi, Namibia, Zambia, and Zimbabwe. Results: Specifically, key drivers of high levels of empowerment among women were household decision-making involvement, female economic independence, and rejecting all reasons for wife-beating. Furthermore, higher levels of women's empowerment in coupled relationships was associated with safer sex negotiation in Malawi (AOR?=?1.57, p?<?0.05) and Zambia (AOR?=?1.60, p?<?0.0001) and sex refusal in Malawi (AOR?=?1.62, p?<?0.0001) and Zimbabwe (AOR?=?1.29, p?<?0.05). However, empowerment was not associated with the likelihood of the male partner having multiple sexual partners across all countries studied. Conclusions: These findings provide evidence that high levels of women's empowerment were associated with safer sex practices, although this varied by country. Policymakers should incorporate empowerment indicators to address women's empowerment and HIV prevention within African couples.